2015
DOI: 10.1021/acs.jpca.5b01563
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Dissociation and Roaming Isomerization of Nitromethane: Experiment and Theory

Abstract: The thermal decomposition of nitromethane provides a classic example of the competition between roaming mediated isomerization and simple bond fission. A recent theoretical analysis suggests that as the pressure is increased from 2 to 200 Torr the product distribution undergoes a sharp transition from roaming dominated to bond-fission dominated. Laser schlieren densitometry is used to explore the variation in the effect of roaming on the density gradients for CH3NO2 decomposition in a shock tube for pressures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 91 publications
4
73
7
Order By: Relevance
“…These were identified by Zhu et al [45] suggesting that the roaming channel is active at pressures lower than 2 Torr over a wide temperature range (400-3000 K). This finding was confirmed by the succeeding study of Annesley et al [23] who also performed shock tube experiments. Their theoretical analysis suggested that at pressures above 2 Torr the product distribution undergoes a sharp transition from the roaming dominated (CH3ONO → CH3O + NO) to the bond-fission dominated (CH3 + NO2) channel.…”
Section: Brief Overview Of Recent Work On the Thermal Decomposition Osupporting
confidence: 54%
See 2 more Smart Citations
“…These were identified by Zhu et al [45] suggesting that the roaming channel is active at pressures lower than 2 Torr over a wide temperature range (400-3000 K). This finding was confirmed by the succeeding study of Annesley et al [23] who also performed shock tube experiments. Their theoretical analysis suggested that at pressures above 2 Torr the product distribution undergoes a sharp transition from the roaming dominated (CH3ONO → CH3O + NO) to the bond-fission dominated (CH3 + NO2) channel.…”
Section: Brief Overview Of Recent Work On the Thermal Decomposition Osupporting
confidence: 54%
“…However, in [31], several recent studies on the thermal CH3NO2 decomposition were not taken into account. In these studies [23,25,[43][44][45], it was suggested that CH3NO2 not only thermally dissociates to CH3 + NO2 but also isomerizes to methyl nitrate (CH3ONO) via a roaming type transition state finally dissociating to CH3O + NO. In 2009, Zhu and Lin [43] studied the CH3NO2 decomposition theoretically and suggested that the channel to CH3O + NO could be detected in experiments.…”
Section: Brief Overview Of Recent Work On the Thermal Decomposition Omentioning
confidence: 99%
See 1 more Smart Citation
“…In the BST, instead of the helium-neon laser originally prescribed by Kiefer, 13 a Fabrey-Perot red diode laser of similar wavelength (637 vs 633 nm) has been employed, following the work of Annesley et al 18 The detector is a quadsegmented photodiode (UDT SPOT-9DMI) with electronics developed and constructed by Argonne National Laboratory.…”
Section: Laser-schlieren Densitometry Diagnosticmentioning
confidence: 99%
“…Since the work of Townsend et al, [1] there has been an explosion of interest in roaming reactions . Most of the initial attention to roaming focused on formaldehyde [1-4, 6-8, 40] and acetaldehyde [5,10,11,15,34,38,41], but more recent studies considered larger carbonyls [12,13,27,32,39], alkanes [14,20,24], ethers [19,26], and NO 2 -containing compounds [22,29,30,33,35,37].…”
Section: Introductionmentioning
confidence: 99%